Cultural Aspects on Child’s Development and Parenting in Manggarai, East Nusa Tenggara, Indonesia - Lon, Yohanes Servatius; Widyawati, Fransiska (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
This paper describes the influence of culture in defining the concept of a child, the stages of development and parenting of children in Manggarai, Flores, East Nusa Tenggara. The main questions are how do Manggaraian people define a child in their culture? How do people divide the stages of child development? What do parenting styles develop by the people to their children? How are these concepts different and similar to the general psychological concept about children? This paper was based on a qualitative research. The methods used were ethnography and grounded theory. Through these two mix approaches, the study is to explore and analyze the culture of Manggarai. The research found that: 1) the concept of a child in Manggarai depends on the way the people understand family and community rather than understand a child as just an individual. 2) There are three main stages of childhood development within the culture of Manggarai; 3) As a patriarchal community, the Manggarai people have unique parenting style to the son and daughter; 4). One unique parenting style within the culture of Manggarai was to educate a child to “fear of spirits and ancestors”.